Catalytic properties of reduced graphene oxide deposited on aluminum and magnesium oxides in acetylene hydrogenation - Nosach, Viktoriia V.; Bychko, Igor B.; Strizhak , Peter Ye. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
The catalytic properties of reduced graphene oxide (rGO) deposited on aluminum and magnesium oxides were investigated in acetylene hydrogenation. Catalysts with different rGO loadings were prepared by impregnating γ-Al₂O₃ and MgO with aqueous graphene oxide suspensions, followed by reduction in hydrogen at 400 °C. The materials were characterized by FTIR, Raman spectroscopy, and SEM. FTIR spectra confirmed the successful deposition of rGO on both supports, and for MgO-based samples, FTIR also revealed partial hydration of surface Mg–O groups, forming Mg(OH)₂ and a hydroxide–graphene interfacial layer that improves anchoring and stabilizes the structure. Raman spectroscopy verified the formation of a graphene-based phase on both oxides and showed that the defect level of the deposited graphene remains constant with varying rGO loading. SEM analysis indicated that on MgO, rGO forms thin film-like structures and irregular folds that create partially covered regions, while on γ-Al₂O₃ it forms continuous films in some areas and isolated folds in others. Modification of γ-Al₂O₃ and MgO with rGO enhanced catalytic activity in acetylene hydrogenation, with the highest rates observed for samples with low rGO content. Both rGO/Al₂O₃ and rGO/MgO exhibited full (100 %) selectivity to ethylene in the 250–400 °C range. The improved performance is attributed to rGO-derived surface structures that ensure effective contact between carbon and oxide phases and facilitate activation of acetylene and hydrogen. Overall, the catalytic behavior of rGO-modified oxides is governed by the acid–base properties of the support and the structural features of the deposited graphene layer, which determine the activation temperature and thermal stability of the system.